Isolation and expression profiles of class III PRX gene family under drought stress in Camellia sinensis - H.J. LI; H.B. WANG; Y. CHEN; Q.P. MA; Z. ZHAO; X.H. LI; X. CHEN (Biologia Plantarum, 2020)
The class III PRX family is a class of heme-containing oxidases and plays important roles in response to abiotic stress in plants. The responses to abiotic stresses could be regulated by phytohormones like abscisic acid (ABA) and methyl jasmonate (MeJA). In this research, 11 CsPRXs genes in tea plant (Camellia sinensis) were cloned and analyzed. Based on the similarity of the sequences, they were classified into 5 sub-groups. According to the results of reverse transcription PCR, CsPRX55 presented the highest expression in roots compared to stems and leaves of both tea cultivars LJ43 and Baiye 1. Besides, the expressions of CsPRX12 and CsPRX73 were highest in roots, while CsPRX4, CsPRX47, and CsPRX72 were highest in stems of 'Baiye 1'. But most of CsPRXs showed the highest expressions in leaves of 'LJ43'. CsPRXs appeared different expression patterns under drought stress of tea plants which were pre-treated with ABA or MeJA for three days. In 'LJ43' and 'Baiye 1', there were 3 CsPRXs and 7 CsPRXs up-regulated by exogenous ABA and MeJA, respectively. However, CsPRX4 and CsPRX16 were down-regulated in 'LJ43' treated with ABA and MeJA. It suggested that CsPRXs possessed diverse functions in response to hormones and abiotic stress. In 'LJ43', the activity of peroxidase (POD) was increased when pre-treated by ABA and MeJA, and the highest activity appeared after 24 and 12 h, respectively. In 'Baiye 1', the activity of POD was also increased, however, when pre-treated by MeJA, the peak-time of POD activity was at 24 h. But the change had no obvious rule after ABA treatment. Exogenous ABA or MeJA may play a role in protecting tea plants suffered from drought stress via regulating some CsPRXs expressions and increasing POD activity.